The New forms of organization and socially responsible business, fundamental for the development of innovation parts (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2016)
Through collaborative work promoting new forms of business organization in an exchange of good wishes to build better organizations better citizens and workers who promote human sense and good practice is generated. To build strong, well-integrated and strengthened organizations use, application and development of the concept of Socially Responsible Company is required, which involves supporting society to protect the environment, generate among employees harmony and quality life through decent wages and environments of collaboration and mutual support for compliance activities. Production processes and results generated from the adoption of new forms of organization in the development of the nested philosophy on the concept of Socially Responsible Company, foster a favorable environment for the generation of new ideas crystallizing innovation. The aim of this paper is to analyze how the new forms of organization presenting the SMEs in the state of Sinaloa, located in Mexico, are helping to get the Socially Responsible Company, and this generates a greater ability to develop innovation processes . The methodology is a documentary research under an analytical approach to help identify the adoption of new forms of organization by the sinaloenses SMEs facilitates the adoption of distinctive Socially Responsible Company. In the results obtained only 20% of SMEs in Sinaloa adopts the distinctive Socially Responsible Company and 70% of them follows a traditionalist model, adopting mechanistic processes that by their nature are very innovative.
Keywords: new forms of organization; socially responsible business; innovation; competitiveness